Analysis of Food Security Status of Fishermen's Households on Kulisusu District North Buton Regency - Rahman, Arif; Limi, Muhammad Aswar; Fyka, Samsul Alam (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study aims to determine the level of household food security in coastal communities. The research was carried out in 2020 in Lantagi Village, Kulisusu District, North Buton Regency. Samples were taken by simple random sampling with a total sample of 35 people. The data analysis used is descriptive quantitative and analysis of food security status using the household food security module developed by the United States Development of Agriculture. The results showed that the level of household food security status of coastal communities was low. This is because most of the fishermen in the research location are classified as poor, and their source of income only relies on fishing activities. Where fishing activities in the sea are also very dependent on traditional fishing gear, sea conditions, waves, weather/seasons. The steps usually taken by fishermen when facing low-income situations so that household food availability remains adequate are buying cheaper food, reducing food consumption, and sometimes borrowing money from family or neighbors.